2021
DOI: 10.3389/fnins.2021.617821
|View full text |Cite
|
Sign up to set email alerts
|

Boldine Attenuates Synaptic Failure and Mitochondrial Deregulation in Cellular Models of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is the most common cause of senile dementia worldwide, characterized by both cognitive and behavioral deficits. Amyloid beta peptide (Aβ) oligomers (AβO) have been found to be responsible for several pathological mechanisms during the development of AD, including altered cellular homeostasis and synaptic function, inevitably leading to cell death. Such AβO deleterious effects provide a way for identifying new molecules with potential anti-AD properties. Available treatments minimally i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
0
6
0
1
Order By: Relevance
“…Additionally, it restored variations in intracellular Ca 2+ levels linked to mitochondria or the endoplasmic reticulum in HT22 cells that had received AbO treatment. It reversed the AbO-induced decrease in mitochondrial respiration in HT22 hippocampus cells, fully recovered the decline in mitochondrial membrane potential, and decreased the rise in mitochondrial reactive oxygen species [50].…”
Section: Anti-alzheimer'smentioning
confidence: 84%
See 1 more Smart Citation
“…Additionally, it restored variations in intracellular Ca 2+ levels linked to mitochondria or the endoplasmic reticulum in HT22 cells that had received AbO treatment. It reversed the AbO-induced decrease in mitochondrial respiration in HT22 hippocampus cells, fully recovered the decline in mitochondrial membrane potential, and decreased the rise in mitochondrial reactive oxygen species [50].…”
Section: Anti-alzheimer'smentioning
confidence: 84%
“…While long-term oral administration of boldine in AD mice revealed preventing the increase in glial hemichannel activity, astrocytic Ca +2 signal, ATP, glutamate release, and alleviated hippocampal neuronal suffering. Another study was performed to investigate the neuroprotective effect of boldine in cellular models (primary hippocampal neurons and HT22 hippocampal derived cell line treated with amyloid beta peptide (Ab) oligomers) of Alzheimer's disease [50]. Results showed that boldine interacts with Ab in silico, preventing its aggregation and defending hippocampus neurons against synaptic failure brought on by AbO.…”
Section: Anti-alzheimer'smentioning
confidence: 99%
“…In addition, boldine attenuates the AβO-induced decrease in mitochondrial membrane potential and mitochondrial respiration as well as the increase in mitochondrial ROS in HT22 hippocampal cells. Therefore, boldine exhibits neuroprotection in an AD model by both direct interaction with Aβ and prevention of mitochondrial dysfunction [ 67 ]. Moreover, boldine can improve the learning and memory of Swiss albino male young and aged mice, possibly by suppressing brain acetylcholinesterase activity and oxidative stress [ 68 ].…”
Section: Improvement Of Brain Functionmentioning
confidence: 99%
“…Neurotoxins such as Aβ, epoxide hydrolase (sEH), dichloroacetic acid, paroxetine, NO, and doxorubicin increase the FR concentration, which is responsible for ROS-induced neuronal cell death and ultimately leads to cognitive impairment and synaptic dysfunction. Administration of neurotoxins disrupts the mitochondrial membrane permeability and alters the calcium homeostasis (Toledo et al 2021;Sheikholeslami et al 2021;Wang et al 2021;Wu et al 2021;Wei et al 2021). To reverse the effects of neurotoxin-induced oxidative stress, the efficacy of antioxidant properties has been tested in both in vivo and in vitro conditions.…”
Section: Synaptic Dysfunction and Synaptic Plasticitymentioning
confidence: 99%